Temperature dependence of the superconducting giant vortex state. Theory and experiment. - de la Cruz, F.; Fink, H. J.; Luzuriaga, J. (American Chemical Society, 1979)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica; Argentina